The shift from typical Western European Late Acheulian to microproduction in unit 'D' of the late Middle Pleistocene deposits of the Caune de l'Arago (Pyrénées-Orientales, France). Issue 135 (October 2019) - Barsky, Deborah; Moigne, Anne Marie; Pois, Véronique
Abstract: Stratigraphic Unit D levels of the Caune de l'Arago (Pyrénées-Orientales, France), situated in the upper part of the depositional sequence of Ensemble Stratigraphique III (ES III), has yielded a rich Acheulian archeopaleontological record dated to the Middle Pleistocene. The site's infill, dated from 690 to 90 ka, encloses a thick cultural sequence comprising some of the oldest evidence of Acheulian documented so far in Western Europe (Unit P levels). The deposits contain successive occupation layers with abundant faunal remains, stone artifacts, and sometimes hominin remains attributed to Homo erectus tautavelensis . The Unit D levels are chronostratigraphically positioned at the top of the ES III sequence, accumulated at the end of Marine Isotope Stage (MIS) 12. The Unit D lithic assemblage shows no evidence of Levallois knapping strategies. Rather, its features indicate a trend towards microproduction that continues into subsequent occupational phases, apparently marking a local expression of the transition from the Lower to the Middle Paleolithic. Remarkably, tiny discoid and multidirectional type cores, predominantly knapped from small-sized quartz pebbles, characterize the Unit D lithic assemblage. Experimental work presented here demonstrates the likelihood that, despite the small size of the cores and the recalcitrant crystalline materials from which they were knapped, flake production can be carried out with free-hand hard hammer techniques. We explore behavioral aspects gleaned from Unit D cultural material, contrasting them with microlithic praxis observed elsewhere in Europe and the Near East in a similar timeframe.